Kontribusi Mahasiswa Dalam Upaya Pencegahan Korupsi - Achmad Asfi Burhanudin (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2019)
Abstract Basically, corruption has a bad impact on the whole joints of human life. Corruption is one of the major causal factors of justice and prosperity of a nation. Corruption also adversely affects the economic system, democracy system, political system, legal system, governmental system, and societal order. No less important corruption can also degrade a nation in international governance. Therefore, we should put corruption as a common enemy that we have to fight together because of its extraordinary nature, then to combat or eradicate corruption is needed extraordinary effort anyway. The effort to eradicate corruption is not at all an easy job. The eradicating corruption effort can not only be the responsibility of law enforcement institutions or government only, but also a responsibility with all the components of the nation. Therefore, the efforts to eradicate corruption should involve all stakeholders that are related, namely government, private and community. It is in this context that students, as one of the important parts of the community, are expected to be active. earnestly. The important contribution of students in the prevention of corruption can not be released from the characteristics they possess, namely: intellectuality, Young Soul, and idealism. Student involvement in the anti-corruption movement can essentially be differentiated into four regions, namely: in the family environment, in the campus environment, in the local community, and at the regional or national level.